The Role of The Tumor Microbiome in Tumor Development and Its Treatment - Chen, Yan; Wu, Fa-Hong; Wu, Peng-Qiang; Xing, Hong-Yun; Ma, Tao (Frontiers in Immunology, 2022)
Commensal bacteria and other microorganisms that reside in the human body are closely associated with the development and treatment of cancers. Recently tumor microbiome (TM) has been identified in a variety of cancers such as pancreatic, lung and breast cancers. TM has different composition in different tumors and has different effects on tumors. TM plays an important role in the formation of tumor microenvironment, regulation of local immunity, and modification of tumor cell biology, and directly affects the efficacy of drug treatment for tumors. TM is expected to be a biomarker for tumors, and engineered tumor-targeting bacteria and anti-cancer microbial agents (GEN-001) have an important role in the treatment of tumors. This paper reviews the relevant studies on TM in recent years and describes its distribution in different tumors, its correlation with clinical features, its effect on local immunity, and the research directions of TM in tumor treatment.